How Does Self Efficacy and Motivation Influence the Adoption of Sexual Abstinence among Students in Indonesia - Pulung Siswantara; Mochammad Bagus Qomaruddin; Tiber Raniar Inner Beauty Bilqis (Wolters Kluwer Medknow Publications, 2024)
In adolescence, dating behavior may escalate into sexual contact which has implications for unwanted pregnancies followed by various negative effects. The purpose of this study was to analyze the effect of self-efficacy on adolescent motivation and analyze the influence of motivation on the adoption of Sexual Abstinence. This study is an observational analytic with a cross-sectional approach, sampling using the Multistage Cluster Random technique with a total of 299 respondents. The data analysis used is Structural Equation Model test at a significance of 0.05. The results showed that there was an influence of self-efficacy variable on motivation with a P value of 0.010 and there was no influence of the motivation variable on the adoption of sexual abstinence with a P value of 0.225. High self-efficacy in adolescents can increase adolescent motivation in adopting sexual abstinence behavior. It takes effort to increase self-efficacy in adolescents which can affect the motivation in adopting sexual abstinence.